The effect of ozone application on the color stability and surface roughness of restorative materials aged with different solutions: an in vitro study - Deniz Sıla Özdemir Çelik; Tuğçe Aslan (BMC Oral Health)
Abstract Background The aim of this study was to investigate the effects of ozone treatment on the color stability and surface roughness of three different restorative materials aged with various beverages. Methods The restorative materials used in this study were alkasite (Cention N-CN), polyacid-modified composite resin (compomer) and resin modified glass ionomer cement (RMGIC), and the aging solutions were orange juice, chocolate milk, cola and control group (distilled water). In this study, 24 groups were determined with n = 10. Vita Easyshade Advance was used for color change measurement and Marsurf M300 profilometer was used for surface roughness measurement on all samples. Half of the groups were applied with ozonated water with Ozonette Dent ozone generator and the other half was not applied. After the ozone procedure, the samples were immersed in the solutions and this process was repeated every day. Color stability and surface roughness measurements were made on days 0, 1, 7 and 14. IBM SPSS V23 programme was used for statistical analyses. Statistically p < 0.05 was considered statistically significant. Results A significant difference was obtained between the 7th day values of the compomer material immersed in orange juice in color change according to ozone application (p = 0.029). There was no statistically significant difference in ∆Ra between ozonated and non-ozonated groups after 14 days. Conclusions The color change of the compomer material immersed in orange juice on the 7th day of ozonated water application was higher than the compomer material without ozonated water application. CN showed the most color change in distilled water, compomer in chocolate milk and RMGIC in cola. CN showed the most color change on the 7th day, while compomer and RMGIC showed the most color change on the 14th day. Ozone treatment had no significant effect on the surface roughness of the restorative materials.